Cyclic lateral load behavior of CFS walls sheathed with different materials - KARAKALE, VAİL (ELSEVIER SCI LTD, 2015)
In recent years, cold formed steel (CFS) buildings have been recognized as viable alternatives to reinforced concrete buildings especially in seismic areas. This is because they are lightweight, fast to construct, recyclable, dimensionally stable, and do not need formworks. Under vertical loading the design principles of these buildings are well established and codified, however, under lateral loadings such as earthquake loads efficient design is needed. In this paper the effects of sheathing material type on the cyclic lateral load behavior of CFS walls were investigated. Ten full scale CFS wall specimens sheathed with four different material types were tested under lateral cyclic loads. The sheathing types are Trapezoidal steel sheet, steel sheet, reinforced cement board, and thin ribbed steel sheet shotcreted with cement mortar. The effect of wall foundation connection details on the lateral load response of the walls were also investigated. Test results indicate that the lateral load carrying capacities of the walls increased by about 3 times when sheathed with the proposed materials. Furthermore specimens sheathed with steel sheets have almost the same lateral load carrying capacities of specimens sheathed with Trapezoidal steel sheets. However the hysteresis damping is higher in the steel sheet sheathed specimens. That means corrugating the steel sheets as Trapezoidal will not increase the strength and damping characteristics of the walls. Walls sheathed with 12 mm thick reinforced cement boards show 1.5 times higher lateral load carrying capacity than all the tested specimens. Depending on the material sheathing type and the sheathing thickness the specimens fail due to local failure in the edge studs, or screw tears out or buckling of the steel sheet. Lastly CFS wall lateral permanent deformations can be reduced by improving the wall-foundation connection details. (c) 2015 Elsevier Ltd. All rights reserved.
Keywords: CFS walls; Sheating type; Cyclic load; Seismic; STEEL; CAPACITY